A repercussão da política nacional de plantas medicinais e fitoterápicos na formação superior em saúde no estado do Ceará entre 2006 e 2016 - Sá, Kellen Miranda (2016)
The National Policy of Medicinal Plants and Phytotherapics (PNPMF), elaborated in 2006 by the Brazilian federal government, through Decree No. 5.813 / 06, established national guidelines and priority lines for the development of actions aimed at guaranteeing the access and rational use of medicinal plants And phytotherapeutics, placing the technical-scientific training of the professionals involved in the entire production chain of medicinal plants as a strategy to provide the population with safe, effective and quality access to this therapy. However, after a decade, it is verified that phytotherapy continues to cause divergences among health professionals. Such situation may be related to deficiencies in academic formation due to the strong influence of the chemosynthesis pharmaceutical industry that directed curricula and the evolution of medical practice in the country. Therefore, the research sought to discover the repercussions generated by the PNPMF in the higher education in health in the state of Ceará, from 2006 to 2016, based on the hypothesis that health professionals (nurses, pharmacists, physiotherapists, physicians, nutritionists and dentists ) Are not fully qualified to work with medicinal plants at graduation and that this constitutes a public health problem. The state of Ceará was chosen because it was consecrated through the pioneering of phytotherapy in public health and served as a model for the rest of the country. The research is a qualitative-quantitative case study, with an exploratory and descriptive approach using the triangulation technique. It promotes a parallel of the information on the health professions, from data of the national curricular guidelines to the higher education institutions of Ceará and the legislations of the class councils, adding the opinions of the different groups involved in the subject of higher education and phytotherapy in and out of the state, since Specialists in the field to health students. In Ceará, there were few advances made by the PNPMF in higher education in health with many undergraduate courses focused on allopathy, which has a negative impact on the labor market and the use of therapeutics, contributing to the consolidation of a worrying scenario. It is necessary to take strategic measures in various areas (education, health, politics and management) to build a future that is in keeping with the health, socioeconomic, cultural and technological reality of Brazil in the twenty-first century. Health professionals in line with a scientifically based herbal medicine in the face of the great advance of the quest for quality of life nowadays.